RETRACTION Riyana, A., Sutapa, P.., Hardianto, D., Pratama, K. W., Utami, D.., Auliana, R.., Utami, D. Y.., Trisnadi, R. A., Astuti, A. T.., Karakauki, M.., Amran, A., Ali, S. K. S.., Suhartini, B. E., Nopembri, S., Irianto, J. P., Razali, M. N.., & Mustapha, A. (2024). La correlación del estatus socioeconómico con la participación de los practicantes de rafting (The Correlation of Socio-Economic Status towards Participation of Rafting Doers). Retos, 52, 225–231. https://doi.org/10.47197/retos.v52.101850 - RETOS, RETOS (Retos, 2025)
Riyana, A., Sutapa, P.., Hardianto, D., Pratama, K. W., Utami, D.., Auliana, R.., Utami, D. Y.., Trisnadi, R. A., Astuti, A. T.., Karakauki, M.., Amran, A., Ali, S. K. S.., Suhartini, B. E., Nopembri, S., Irianto, J. P., Razali, M. N.., & Mustapha, A. (2024).  La correlación del estatus socioeconómico con la participación de los practicantes de rafting (The Correlation of Socio-Economic Status towards Participation of Rafting Doers). Retos, 52, 225–231. https://doi.org/10.47197/retos.v52.101850Retraction of the article by the editor of the journal. There has been several clear and conclusive proofs that there has been a manipulation of the authorship of the article. The accepted Word document was sent with the names of the authors that appeared in the “Corrections for the edition” message so that they could only make the orthographical corrections that were necessary. The corresponding author (or whoever hurt him) changed the authors of the aforementioned Word document that was sent to them, returning a document together with these corrections made with new authors, all without any express notification, without any document explaining the changes made accepted by all the authors and, of course, without express authorization from the journal Retos between both moments. With this fraudulent document the galleys were made and the article was definitively published, assigning it the corresponding DOI.Authors in the Word document of the article submitted for review: 15Authors in the published PDF with modified authors: 17Differences between the authors between both moments: +3 y -1 (Additions: Syed Kamaruzaman Syed Ali, Muhammad Nazim Razali, Aida Mustapha. Eliminated: Deni Hardiano)